ASAS KEBEBASAN BERKONTRAK DAN ASAS KEPRIBADIAN DALAM KONTRAK-KONTRAK OUTSOURCING - Taufiq El Rahman; R. A. Antari Innaka; Ari Hernawan; Ninik Darmini; Murti Pramuwardhani Dewi (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2011)
The freedom of contract applies for parties n outsourcing contracts, even though it is not applicable for outsourcing worker. There are violation in personality principle where the outsourcing contract is applicable for third party. The legal protection for outsourcing worker is also weak. Asas kebebasan berkontrak berlaku bagi para pihak dalam perjanjian outsourcing tetapi tidak berlaku bagi tenaga kerja outsourcing. Terdapat penyimpangan terhadap asas kepribadian, dimana perjanjian outsourcing berlaku bagi tenaga kerja outsourcing yang berkedudukan sebagai pihak ketiga. Perlindungan hukum bagi tenaga kerja outsourcing relatif lemah.